Mampukah Mewujudkan Pendidikan Inklusif Pemuda Penghayat Kepercayaan di Indonesia? Problematika dalam Lensa Hukum Progresif dan Teori Pengakuan - Aji Baskoro (Universitas Gadjah Mada, 2025)
Despite Constitutional Court Decision No. 97/PUU-XIV/2016 affirming their constitutional rights, fulfilling educational access for youth adherents of indigenous beliefs remains a critical issue in Indonesia. The primary obstacles include administrative discrimination, the absence of relevant curricula, and social stigma limiting inclusive education. This study employs a juridical-empirical method with socio-legal, historical, and statutory approaches, utilizing Progressive Law and Recognition Theory as analytical frameworks. Data were collected through interviews with parents and education officials in Sumba, alongside an analysis of primary and secondary legal materials. Findings reveal a sharp gap between juridical legitimacy and field implementation, where Marapu youth face structural discrimination and social misrecognition. Bureaucratic formalism compels identity coercion, while exclusive curricula alienate students. Consequently, this study recommends progressive legal transformation through policy breakthroughs and strengthened socio-cultural recognition to achieve substantive inclusive education.